Gender Analysis in Higher Education Access in Remote Areas - Pijoh, Feibe Engeline (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2025)
The purpose of this study is to analyze gender dynamics in access to higher education in remote areas of Indonesia, focusing on structural barriers, cultural constructs, and community adaptation strategies. The research method uses a qualitative approach with a systematic literature review of publications from 2014-2024 from various electronic databases including Science Direct, Scopus, Google Scholar, and Web of Science. Data analysis was conducted through a thematic approach that integrates an intersectional perspective to understand the complexity of gender issues in the context of higher education in remote areas. The results reveal that structural barriers include limited technological infrastructure, inaccessible financing systems, and institutional biases that create multiple disadvantages for communities in remote areas with different impacts based on gender. Cultural constructs regarding traditional gender roles interact with geographic and economic factors to create different expectations and limitations for women and men. Communities in remote areas develop innovative adaptation strategies including informal mentorship systems, community support networks, and the collective use of digital technology to overcome barriers to accessing higher education. The findings demonstrate the need for a multidimensional approach that integrates structural interventions with community empowerment to achieve gender equality in access to higher education in remote areas.